Reversal in Solvatochromism, Photochromism and Thermochromism in a New Bis-azo Dye Based on Naphthalen-1-amine - Sıdır, İsa; Kara, Yunus Emre; Sıdır, Yadigar Gülseven; Berber, Halil; FAUSTO, RUI (Elsevier B.V., 2024)
A novel bis-azo dye, 4,4′-((1E,1′E)-(oxybis(4,1-phenylene))bis(diazene-2,1-diyl))bis(naphthalen-1-amine) (abbreviated as 4odna) was synthesized and characterized by IR and 1H, 13C and 2D COSY-NMR spectroscopies, and mass spectrometry. Optical properties were evaluated using UV–vis absorption spectroscopy. The observed solvatochromism was ascribed to the presence of different azo or/and hydrazone forms in solution. The azo forms show both positive and negative solvatochromism, with the reversal occurring for solvents with ET(30) ∼45 kcal mol−1, while the hydrazone tautomer shows negative solvatochromism. Application of the multiparametric Catalán and Kamlet-Taft linear solvation energy models allowed to evaluate the dependence of the solvatochromism exhibited by 4odna on the hydrogen bond donating (HBD) and accepting (HBA) abilities of the solvent, as well as on their dipolarity (SdP) and polarizability (SP). Upon UV (λ = 311 nm) irradiation at room temperature, the compound was found to exhibit similar photochromic behavior in the polar-protic solvents methanol and ethanol, which is distinct from that observed in the polar-aprotic solvents dichloromethane, chloroform and chlorobenzene, with the hydrazone tautomer being photoconverted into the azo tautomer in the first group of solvents and vice-versa in the second group. In acetone, UV irradiation extensively transforms the compound into species with no absorption in the visible range, leading to fast discoloration of the solution. Temperature dependence of the color of the solutions of 4odna in ethanol and chlorobenzene was also evaluated, and reversible thermochromic behavior was observed in the first solvent. In chlorobenzene, no thermochromism was observed, but a change of color of the solution was promptly induced by the UV–vis broadband source beam of the spectrometer when the absorbance spectrum of the solution was being recorded at T = 115 °C, which demonstrates that the azo forms of 4odna undergo easy phototransformation into the hydrazone forms in this solvent at high temperature. © 2023 Elsevier B.V.
Keywords: Azo Dye; Hydrogen Bonding; Photochromism; Reversal in Solvatochromism; Solvent Effects; Thermochromism